Retroviruses and human disease. Issue 9 (September 1987) - Weiss, R A
Abstract : Over the past 25 years animal retroviruses have been favoured subjects of research by virologists, oncologists, and molecular biologists. Retroviruses have given us reverse transcriptase, oncogenes, and cloning vectors that may one day be exploited for human gene therapy. They have also given us leukaemia and the acquired immune deficiency syndrome (AIDS). Kawasaki disease and tropical spastic paraparesis are thought to be associated with retrovirus infection, and other diseases such as de Quervain's thyroiditis, multiple sclerosis, acquired hypogammaglobulinaemia, and certain forms of non-A, non-B hepatitis have come under passing suspicion of a retroviral aetiology. With AIDS threatening to become pandemic, and a second AIDS virus appearing in West Africa, human retroviruses are under intensive study for new antiviral drugs targeted to their unique mode of replication, and for the development of vaccines.